Reinventing the Theatre Curriculum to Address Contemporary Development Needs and Job Alignment in Nigeria. - Esekong Andrew-Essien (Universitas Negeri Makassar, 2021)
As the social and economic terrain is changing in Nigeria, theatre training and practice have not evolved commensurately to address the current development needs and job alignment. The models used in many Nigerian universities mainly offer theoretical knowledge of theatre and basic training for entertainment roles. Even though the philosophy and objectives of theatre training in the NUC Benchmark for minimum academic standards are couched with the anticipation for innovation and programme expansion, it does not specify the type or scope of expansion needed to retain the viability of theatre practice within the current knowledge economy. Nigerian universities are therefore not firmly guided to develop their theatre curricula in a direction that is sensitive to the exigencies of time and age. There is currently a lot of interest in film production, carnival, standup comedy, development communication, applied theatre and event management. This paper argues that theatre and performing art programmes in universities and other theatre training centres should develop more courses around these emerging areas of interest. The paper submits that while there are many specialties in which theatre graduates can be professionally engaged, and while the nature of theatre training imbues numerous subjective qualities desired in the contemporary world of work, much more could be done by reinventing the theatre curriculum to give theatre graduates wider opportunities.